Humic acid promotes arsenopyrite bio-oxidation and arsenic immobilization - Zhang, Duo-rui; Chen, Hong-rui; Xia, Jin-lan; Nie, Zhen-yuan; Fan, Xiao-lu; Liu, Hong-chang; Zheng, Lei; Zhang, Li-juan; Yang, Hong-ying (Journal of hazardous materials, 2020)
[Display omitted] •The effect of humic acid (HA) on bio-oxidation of FeAsS was first studied.•HA simultaneously promotes FeAsS dissolution and As immobilization.•The flocculent porous structure favors to FeAsS dissolution in the presence of HA.•A new way was provided for As immobilization in FeAsS bio-treatment. The bio-oxidative dissolution of arsenopyrite, the most severe arsenic contamination source, can be mediated by organic substances, but pertinent studies on this subject are scarce. In this study, the bio-oxidative dissolution of arsenopyrite by Sulfobacillus thermosulfidooxidans and arsenic immobilization were evaluated in the presence of humic acid (HA). The mineral dissolution was monitored through analyses of the parameters in solution, phase and element speciation transformations on the mineral surface, and arsenic immobilization on the surfaces of cells and jarosites-HA. The results show that the presence of HA enhances the dissolution of arsenopyrite, e.g., 7.1% of arsenopyrite was in the residue after 12 d of bio-oxidation compared to 19.3% in the absence of HA. Meanwhile, the presence of HA led to changes of the fates of As and Fe and no accumulation of elemental sulfur (S0) or ferric arsenate on the mineral surface. Moreover, a flocculent porous structure was formed on the surfaces of both microbial cells and jarosites, on which a large amount of arsenic was adsorbed. These results clearly indicate that HA can simultaneously promote the dissolution of arsenopyrite and arsenic immobilization, which may be significant for bioleaching of arsenopyrite-bearing contaminated sites.